Nationalism, Zionism and ethnic mobilization of the Jews in 1900 and beyond - Berkowitz, Michael (IJS studies in Judaica ;, 2004)
European, US, and Israeli historians and social scientists try to skirt the political controversies involved in the origin of Israel to offer academic perspectives on Jewish nationalism, of which Zionism comprised a prominent alternative beginning in the late 19th century. They look in particular at aspects that have been undervalued in examining J.